Exploration of Biomimetic Metal-Organic Catalysts for Splitting Glucose into Dihydroxyacetone and Glyceraldehyde - Sumargo, Margaretha; Audreylia, Vanessa; Luivan, Samuel; Susanti, Maria Patrycia Della; Soerawidjaja, Tatang Hernas; Hudaya, Tedi (Directorate for Research and Community Services, Institut Teknologi Bandung, 2025)
Lactic acid is a metabolite produced during glucose glycolysis, typically generated industrially through the fermentation of glucose using microorganisms. However, the high production cost of this fermentation process makes lactic acid relatively expensive, rendering biodegradable plastics made from polylactic acid less competitive. This research focuses on the initial stages of glucose glycolysis process, in which glucose is split into dihydroxyacetone and glyceraldehyde, both of which are isomers of lactic acid. Biomimetic metal-organic catalysts composed of Mg-Zn tripolyphosphate, imidazole, and monosodium or monoammonium glutamate were tested in a water–acetonitrile reaction medium. Prior to catalyst testing, either water–acetonitrile or water–acetonitrile–acetone solutions were chosen as the reaction medium based on their effectiveness in producing phase separation. The study investigated the effects of catalyst concentrations, catalyst types, and reaction temperatures on glucose conversion, as well as the yield and selectivity of dihydroxyacetone and glyceraldehyde within 6 hours reaction time at pH 8. The results showed that these biomimetic metal-organic catalysts effectively facilitated the splitting of glucose in a water–acetonitrile solution, achieving the best glucose conversion of 57.16% at a temperature of 90°C with a catalyst concentration of 0.8%-mol.